Pyrolysis and combustion of a solid refinery waste. (1st May 2020) - Senneca, O.; Chirone, R.; Cortese, L.; Salatino, P.
Highlights: Characterization of refinery wastes from a hydro-catalytic process. Pyrolysis and oxidative pyrolysis of Mo rich fuel are different. Oxygen is uptake in the early stages of pyrolysis. Molybdenum is retained during pyrolysis at 600 °C. Is lost during combustion. Char combustion reactivity in fluidized bed is low. Abstract: This study addresses pyrolysis and combustion of a heavy hydrocarbon residue of the refinery industry. The material has good calorific value (HHV = 34050 kJ/kg), is solid at room temperature and has a high content of metals, in particular Mo, and impurities. The effect of these metals on pyrolysis and combustion has been investigated. The activity included first of all the physical and chemical characterization of the raw sample before and of samples of char and ash by means of several techniques: ICP, SEM EDAX. Moreover pyrolysis and combustion have been investigated by TGA and in small scale reactors of the fixed and fluidized bed type. Mo, very abundant in the raw sample, is relatively stable upon pyrolysis at 500–600 °C, but is only marginally retained in the ash after combustion, because of the large volatility of this metal in the oxidized state. The metal content has interesting effects on the pyrolysis and char combustion behavior: when the sample is heated up under mildly oxidizing atmospheres (i.e oxygen concentration of < 1%), the metals promote the uptake of oxygen in parallel with char formation and affect the degree of graphitization of the carbon structure The composition of the pyrolysis gas is strongly affected by the presence of even low concentration of oxygen. Despite the fact that a catalytic action of the metals could be expected, reaction times in a fluidized bed reactor are relatively large compared to other conventional and non conventional solid fuels.